2019
DOI: 10.26681/jote.2019.030205
|View full text |Cite
|
Sign up to set email alerts
|

Online Hybrid vs. Face-to-Face Instruction in Applied OT Theory

Abstract: Minimal evidence exists regarding online education in occupational therapy. This study explored entry-level occupational therapy (OT) student responses to two methods of instruction in an applied OT theory course. The investigator used a retrospective quasi-experimental, nonrandomized comparison group design with mixed methods to compare two cohorts of entry-level OT students. Data included midterm exam, final exam, and cumulative course grades, as well as qualitative data from a final exam essay question. Dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…This is in line with the blended learning designs having a more effective or equivalent effect than the F2F class on the learning outcome in PT education, as reported by Ødegaard et al [13]. In addition, students in the blended learning design studies reported subjective opinion such as improvement of communication between students, appropriate course design and online learning environment to achieve learning outcomes, and improvements in autonomy and active participation [25][26][27]30,37]. This is consistent with the results of previous studies that framed learning goals; the use of technology to support achievement of those goals in education improves student engagement, student-student communication, student-instructor communication, and promotes critical discussion [48,49].…”
Section: Digital Learning Designs and Outcomessupporting
confidence: 83%
See 4 more Smart Citations
“…This is in line with the blended learning designs having a more effective or equivalent effect than the F2F class on the learning outcome in PT education, as reported by Ødegaard et al [13]. In addition, students in the blended learning design studies reported subjective opinion such as improvement of communication between students, appropriate course design and online learning environment to achieve learning outcomes, and improvements in autonomy and active participation [25][26][27]30,37]. This is consistent with the results of previous studies that framed learning goals; the use of technology to support achievement of those goals in education improves student engagement, student-student communication, student-instructor communication, and promotes critical discussion [48,49].…”
Section: Digital Learning Designs and Outcomessupporting
confidence: 83%
“…The online materials used were not intended to replace the F2F class session, but to supplement the content discussed in the classroom [18]. The blended courses in this review showed similar or improvement in learning outcomes compared to the F2F group [24,25,30,38]. This is in line with the blended learning designs having a more effective or equivalent effect than the F2F class on the learning outcome in PT education, as reported by Ødegaard et al [13].…”
Section: Digital Learning Designs and Outcomessupporting
confidence: 60%
See 3 more Smart Citations